2012
DOI: 10.1080/1350293x.2012.650011
|View full text |Cite
|
Sign up to set email alerts
|

Practicum assessment of culturally and linguistically diverse early childhood pre-service teachers

Abstract: Refugees, 2004) although a thorough review of this literature is beyond the scope of this paper. This study draws primarily on initial teacher education literature about the need for teacher education programs to prepare culturally sensitive and competent pre-service teachers (Allard & Santoro, 2004; Ball, 2000; Milner, 2003). This overview reveals there is little research about the cultural competence of teacher educators, including teachers in early childhood services who play a significant role in the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The research of Ortlipp (2003) and Nuttall and Ortlipp (2012) establishes the potential for 'silence' within the practicum assessment, in which participants feel that they cannot, or should not, share all that they would wish to in the assessment process. To explore this issue, each participant was directly asked if they felt that they were openly able to share their point of view within the assessment meetings.…”
Section: Case Study Toru: Assessment and The Silencing Of Voicesmentioning
confidence: 99%
“…The research of Ortlipp (2003) and Nuttall and Ortlipp (2012) establishes the potential for 'silence' within the practicum assessment, in which participants feel that they cannot, or should not, share all that they would wish to in the assessment process. To explore this issue, each participant was directly asked if they felt that they were openly able to share their point of view within the assessment meetings.…”
Section: Case Study Toru: Assessment and The Silencing Of Voicesmentioning
confidence: 99%
“…Not surprisingly, by the end of the program most of the students purged any of their cultural practices and beliefs that competed with the notion of the "good" early childhood educator, retaining only superficial signifiers of their cultural identities in practice. In Australia, Nuttall and Ortlipp (2012) interviewed culturally and linguistically diverse students after their field placements. Positioned by her supervisor within a discourse of "difference as deficit," one student commented that she needed to "become someone she would not be 'in real life'" in order to pass her placement (p. 57).…”
Section: Culturally and Linguistically Diverse Ecte Students And Educmentioning
confidence: 99%
“…Immigrant and refugee women may experience an especially profound dissonance between the Euro-North-American content and expectations of the program and their own cultural beliefs, knowledges, experiences, and values (Gupta, 2006). Previous research has suggested that these women feel compelled to adopt program expectations at the expense of their own beliefs (Moles, 2014;Nuttall & Ortlipp, 2012).…”
mentioning
confidence: 99%
“…Rehearsal was a targeted skill set given that it is a salient theme in the literature. CALD students' preference on field experience is to observe, rather than to participate (Iyer & Reese, 2013;Nuttall & Ortlipp, 2012;Spooner-Lane et al, 2009). That is, they tend towards "peripheral participation" rather than participation (Iyer & Reese, 2013, p. 34).…”
Section: The Projectmentioning
confidence: 99%
“…Increasing diversity in student populations requires attention to culturally responsive teaching and learning, and considerations of student experiences of coursework and field placements within degree programs (Harrison & Ip, 2013;Mak & Barker, 2013). For students from culturally and linguistically diverse (CALD) backgrounds, research indicates that field placements in particular can produce unique challenges, including communication and language barriers, unfamiliarity with the Australian context and colloquialisms, interpreting how field supervisors define success, and assessment by way of western standards of graduate proficiency (Nuttall & Ortlipp, 2012;Ortlipp & Nuttall, 2011;Spooner-Lane, Tangen, & Campbell, 2009). For both university staff and field supervisors, there are additional cognitive and affective demands of intercultural competence necessary for effective approaches to teaching and learning and the supervision of CALD students in the field.…”
Section: Introductionmentioning
confidence: 99%